Effects of temperature and repeat layer spacing on mechanical properties of graphene/polycrystalline copper nanolaminated composites under shear loading - Huang, Chia-Wei; Chang, Man-Ping; Fang, Te-Hua (Beilstein Journal of Nanotechnology, 2021)
In the present study, the characteristics of graphene/polycrystalline copper nanolaminated (GPCuNL) composites under shear loading are investigated by molecular dynamics simulations. The effects of different temperatures, graphene chirality, repeat layer spacing, and grain size on the mechanical properties, such as failure mechanism, dislocation, and shear modulus, are observed. The results indicate that as the temperature increases, the content of Shockley dislocations will increase and the maximum shear stress of the zigzag and armchair directions also decreases. The mechanical strength of the zigzag direction is more dependent on the temperature than that of the armchair direction. Moreover, self-healing occurs in the armchair direction, which causes the shear stress to increase after failure. Furthermore, the maximum shear stress and the shear strength of the composites decrease with an increase of the repeat layer spacing. Also, the shear modulus increases by increasing the grain size of copper.
Keywords: dislocation; graphene/Cu; molecular dynamics; shear; self-healing